Association of uric acid as a risk factor in ischemic stroke – A hospital-based observational study - Jegan Mohan Yogiswaran; Sasthanathan Ganesan; Sathyan Elangovan (Asian Journal of Medical Sciences, 2022)
Background: The second most prevalent cause of mortality globally, next to coronary artery disease, is stroke. In humans, uric acid is the final catabolite in the metabolism of purine. Aims and Objectives: The aims of this study were to determine the importance of blood uric acid levels in stroke patients in South Indian population. Materials and Methods: In this observational study, we evaluated acute stroke patients who were admitted to Melmaruvathur Adhiparasakthi Institute of Medical Sciences and Research (MAPIMS) Hospital from December 2021 to May 2022. One hundred patients meeting the inclusion standards were enrolled and divided into two groups randomly following acquisition of ethical approval and informed consent. Results: In our study consisting of both study and control groups, low-density lipoprotein cholesterol (P=0.034), non-high-density lipoprotein cholesterol (HDL-C) (P=0.0127), total cholesterol (P=0.0196), HDL-C (P=0.042), and triglyceride (P=0.0266) were found to be statistically significant. Mean serum uric acid (SUA) level between cases (6.94±1.97 mg/dL) and controls (5.49±1.27 mg/dL) were also statistically significant (P=0.0306 and P=0.049). Conclusion: Our study showed that stroke patients had a significant occurrence of hyperuricemia. In keeping cardiovascular risk factors such as diabetes, hypertension, triglyceride level, total cholesterol level, coronary heart disease, and tobacco use under control, SUA was observed to be substantially linked with the initial phase of ischemic stroke.